CSIG-07. GAIN-OF-FUNCTION MUTANT P53 REGULATES LONG-NONCODING RNAS IN GLIOBLASTOMA. (14th November 2022) - Zhang, Ying; Yuan, Feng; Grello, Cassandra; Reon, Brian; Gibert, Myron; Dube, Collin; Dutta, Anindya; Holland, Eric; Abounader, Roger
Abstract: P53 is frequently mutated in most human cancers, including glioblastoma (GBM). Many p53 mutants acquire gain-of-function oncogenic effects through only partially understood mechanisms. To investigate the role of gain-of-function mutant p53 (MUT-p53) in GBM, we performed ChIP-seq of wildtype p53 (WT-p53) and MUT-p53 GBM cell lines. Among 2834 unique peaks reads in MUT-p53 cells, we found 242 long non-coding RNAs (lncRNAs) with up to 145 fold enrichment relative to WT-p53. LncRNAs regulate many molecular and cellular functions, including gene expression, cell proliferation, death, cancer stem cell renewal and differentiation. We selected lncRNAs SOX21-AS1 and LINC00643 with highly enriched binding by MUT-p53 and investigated their expressions and functions in the p53 pathway. We performed ChIP confirmation of MUT-p53 binding to the promoters of these lncRNAs. We found that these lncRNAs are deregulated in GBM and correlated with GBM patient survival in the TCGA database. To investigate the functions of these LncRNAs, we knocked down their expressions by siRNA, and found significant cell death induced by si-SOX21-AS1, but not by si-LINC00643. Overexpression of LINC00643 in GBM cells led to inhibition of GBM cell proliferation, migration, invasion and in vivo xenograft growth. LINC00643 mediated the effects of MUT-p53. Co-expression of human LINC00643 and its mouse homologous in a RCAS transgenic mouse model of GBM reduced tumor growth and improved animal survival. To elucidate the mechanisms of action of the lncRNA, we performed Chromatin Isolation by RNA purification high-throughput sequencing (CHIRP-seq) to identify its binding targets. We found that LINC00643 binds to HIF1a 5' promoter/enhancer region. Overexpression of LINC00643 in GBM cells at hypoxia growth condition reduced HIF1a mRNA and protein expression. Our study shows for the first time that gain-of-function mutant p53 regulates a subset of lncRNAs and that the lncRNAs mediate the oncogenic effects of the MUT-p53 in GBM.